A new species in the tortoise-beetle genus Dorynota s. str. Chevrolat (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini) from Brazil - Simões, Marianna V. P.; Sekerka, Lukáš (Zootaxa, 2023)
A new species Dorynota phoenix Simões and Sekerka, new species is described and figured from Mato Grosso state of Brazil. The new species belongs to the D. monoceros species-group and is compared to morphologically similar taxa. Updated key to the nominotypical subgenus of Dorynota is provided.